A non-traditional open-source solution for altmetrics. Issue 5 (23rd September 2021) - Jamwal, Vineet; Kaur, Simran
Abstract : Purpose: Altmetric carries the potential of highlighting scholarly content by measuring online interactions much before other forms of traditional metrics grow up. The aim of this paper is to be the single point of access for librarians, scientists, information specialists, researchers and other scholars in public to learn to embed the open-source embeddable badge provided by Altmetric in their websites and showcase their article altmetrics. Libraries can take advantage of this free and innovative tool by incorporating it in their own websites or digital repositories. Design/methodology/approach: This paper elucidates steps for embedding altimetric institutional repository badges in personal websites or institutional repositories. Findings: This open-source Altmetric tool tracks a range of sources to catch and collect the scholarly activity and assists in monitoring and reporting the attention surrounding an author's work in a very timely manner. Originality/value: This tool is freely available to libraries worldwide.